OPTIMIZED BINDER SOLUTION PROTECTIVE COATING AND FACTORS OF ITS WIND RESISTANCE AND EFFICIENCY (Academicia Globe: Inderscience Research, 2022)
The article notes the production of a wind-resistant protective coating to protect roads from sand slippage in a new way: fixing moving wet sands with an existing solution.